Two feet, four paws the girl who walked her dog 4,500 miles - Talbot-Ponsonby, Spud (Summersdale, 1999)
Take one feisty girl, a dog and a camper van called "Spudtruck" and set them off on a journey around Britain's coastline, the equivalent distance of London to Calcutta, to raise almost 44,000 for the charity "Shelter", and revel in the honest descriptions of the true state of our island.